Research Trends on Intellectual Property And Contribution of Arab Countries: Scientometric analysis of Publications Indexed in the Scopus Database (1993-2022) - ABADA, Chahrazed (Journal of Human Sciences, 2025)
Papers indexed in the Scopus database from 1993 to 2022 was used for scientometric analysis on intellectual property, revealing the quantitative distribution by year, language and type of publication of 4489 documents; Also the contribution of Arab countries has been studied, the analysis of the collaboration of Arab authors and the analysis of the co-occurrence of keywords are analyzed via the VOSviewer software.The results show that intellectual property publications have experienced sustained growth through 2011 and fluctuations from 2012 to 2022; that the USA, UK and China are the most active countries; the contribution of the Arab countries is very minimal (2%) compared to the world production, Egypt, the Arab Emirates and Saudi Arabia are the best ranked.